1985
DOI: 10.1071/pp9850059
|View full text |Cite
|
Sign up to set email alerts
|

CO2Enhancement of Aerobic and Hypoxic C2H4 Production in the Tissues of Cocklebur Seeds at Different Dormant States

Abstract: CO2 stimulated C2H4 production in the axial and cotyledonary tissues of cocklebur (Xanthium pensylvanicum Wallr.) seeds regardless of their dormant states. Axial tissues were more responsive to CO2 than cotyledonary ones, and the tissues of upper seeds were more responsive than those of lower ones. Responsiveness of upper seed tissues to CO2 increased in the following order: primarily dormant (PD), non-dormant (ND) and secondarily dormant (SD) and also with increasing the period of presoaking. The CO2 stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In order to examine whether the germinationinhibiting elTect of C2H4 at higher temperatures was due to the inhibition of axial growth by C2H4, the axial segments excised from seeds pre-soaked for 1 week were incubated at 33 °C with C2H4 at various eoncentrations ranging from 0.01 to 30 cm^ m~^ in air or under 0.05 m^ m"^ O2, The hypoxic condition was adopted to restrain CO2 output from the segments to a minimum, for the CO2 output of cocklebur seeds was minimized at ca, 0,05 m-' m~Ô 2 (Esashi et al, 1985), However, an inhibition of axial growth by C2H4 at 33 °C was not detected over its concentration range (data not shown). As shown in Table 3, C2H4 had no influence on the axial growth at 33 °C even at 3 cmm~^, which was significantly effective in stimulating it at 23 °C Esashi et ai, 1976Esashi et ai, , 1978.…”
Section: Control Of Axial Growth By C2h4mentioning
confidence: 99%
“…In order to examine whether the germinationinhibiting elTect of C2H4 at higher temperatures was due to the inhibition of axial growth by C2H4, the axial segments excised from seeds pre-soaked for 1 week were incubated at 33 °C with C2H4 at various eoncentrations ranging from 0.01 to 30 cm^ m~^ in air or under 0.05 m^ m"^ O2, The hypoxic condition was adopted to restrain CO2 output from the segments to a minimum, for the CO2 output of cocklebur seeds was minimized at ca, 0,05 m-' m~Ô 2 (Esashi et al, 1985), However, an inhibition of axial growth by C2H4 at 33 °C was not detected over its concentration range (data not shown). As shown in Table 3, C2H4 had no influence on the axial growth at 33 °C even at 3 cmm~^, which was significantly effective in stimulating it at 23 °C Esashi et ai, 1976Esashi et ai, , 1978.…”
Section: Control Of Axial Growth By C2h4mentioning
confidence: 99%
“…Negm et al (22) have reported that C2H4 requires a minimum endogenous level of CO2 for overcoming the high temperatureinduced secondary dormancy oflettuce seeds. On the other hand, in cocklebur seeds, the respiration activity and C2H4 production decrease with the development of secondary dormancy (10), but the C02-enhancement ofC2H4 production increases ( 12). Neither CO2 or C2H4 applied singly could stimulate the germination of secondarily dormant cocklebur seeds.…”
mentioning
confidence: 99%